Linking plant composition and arthropod abundance to establish little bustard breeding requirements in pastureland dominated landscapes - Faria, Nuno; Rabaça, João E.; Morales, Manuel B. (Biodiversity and Conservation, 2012)
Most research on steppe bird habitat selection has been focused on the effects of management regimes or vegetation structure. However, much less is known on how plant composition is related with steppe bird occurrence. We investigated microhabitat of little bustard territorial males and females during the nesting and chick-rearing season in areas with dominance of pastureland focusing on plant composition. We searched for relationships between preferred vegetation and arthropod abundance in order to identify the contribution of different vegetation typologies in providing essential trophic resources for the species. Surveys of little bustards were made using car and foot transects. Plant composition was obtained within a 50 9 50 cm square at four sampling replicates and arthropod availability was sampled using a sweep net. Statistical procedures were conducted in three steps: (1) analysis of variance was used to identify at univariate level the plant composition and arthropod variables that were signiﬁcantly related with both male and female occurrence sites; (2) principal components analysis was performed using the variables with signiﬁcant results at univariate level; (3) model averaging on generalized linear and mixed models was applied to evaluate the selection probability of each principal component. The species occurs in sites with high ﬂoristic richness and high abundance of Fabaceae species, although plant composition differs from male to female sites. These variables were found to be crucial to provide higher abundances of arthropods, notably of Acrididea, Formicidae and some groups of Coleoptera which are decisive for the selection of displaying or female breeding sites.
Keywords: Acrididae; Fabaceae; grassland; Microhabitat selection; Plant richness; Tetrax tetrax

Determination of Poly(ethylene glycol)-Binding to Browse Foliage, as an Assay of Tannin, by Near-Infrared Reflectance Spectroscopy - Landau, Serge; Dvash, Levana; Decandia, Mauro; Cabiddu, Andrea; Shapiro, Fira; Molle, Giovanni; Silanikove, Nissim (Journal of Agricultural and Food Chemistry, 2004)
Nutritionists are interested in functional assays of tannins that do not require time-consuming and expensive extraction, such as the 14C-labeled poly(ethylene glycol) (PEG)-binding (PEG-b) assay. This paper reports the application of near-infrared (NIR) spectroscopy to determine the percentage of PEG binding, in place of the 14C-labeled PEG-b assay of tannin, in Mediterranean woodland vegetation. Calibration was done with 53 samples from 14 species and was validated on 25 samples from 10 species. PEG-b ranged between 1.4 and 20.7% in the samples. The calibration obtained by using the modified partial least-squares (MPLS) method, with all wavelengths in the 1100?2500 nm range combined, and the validation were reasonably linear (R?2 = 0.96 and 0.91, respectively). The accuracies, estimated from the standard errors of cross-validation and prediction, were ±1.6 and ±1.7% PEG-b, respectively. The NIRS-aided procedure proposed here can serve as an accurate, inexpensive, time-saving, and environment-friendly functional assay of tannin in Mediterranean browse. Keywords: NIRS; goats; nutrition; poly(ethylene glycol); pasture
From Duplicate 1 (Determination of Poly(ethylene glycol)-Binding to Browse Foliage, as an Assay of Tannin, by Near-Infrared Reflectance Spectroscopy - Landau, Serge; Dvash, Levana; Decandia, Mauro; Cabiddu, Andrea; Shapiro, Fira; Molle, Giovanni; Silanikove, Nissim)
Keywords: Animal Nutritional Physiological Phenomena; Animals; Carbon Radioisotopes; Fabaceae; Fabaceae: chemistry; Goats; Hydrolyzable Tannins; Hydrolyzable Tannins: analysis; Near-Infrared; NIRS; nutrition; pasture; poly(ethylene glycol); Polyethylene Glycols; Polyethylene Glycols: metabolism; Spectroscopy